EVALUATION OF OUT-OF-HOME LAST-MILE DELIVERY METHODS IN TERMS OF SUSTAINABILITY - Yılmaz, Şaban Fatih; Demirel, Neslihan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Last-mile (LM) delivery takes place in the last stage of supply chains in the city centers and directly affects the sustainability of urban areas. Besides affecting the sustainability of the urban, since managing LM delivery is the most complicated and expensive stage in supply chains, it has to be explored, and solutions should be developed in terms of sustainability. In this study, as an alternative to traditional home delivery of parcels, the evaluation of six different out-of-home delivery methods (parcel locker, pick-up point, click & collect, in-car (trunk) delivery, reception/delivery box, and pick-up/drop-off point) has been carried out. The Hesitant Fuzzy Linguistic Term Sets approach has been applied for the evaluation of alternatives with the aim of eliminating the uncertainty and hesitation in expert opinions. Considered criteria in the proposed methodology have been determined with detailed literature research and expert opinions. Click & Collect has obtained the highest value in terms of sustainability among the options analyzed in the study. Sensitivity analyzes have been conducted to assess the results' sensitivity in terms of sustainability.